The Transplant Evaluation Rating Scale Predicts Clinical Outcomes 1 Year After Lung Transplantation: A Prospective Longitudinal Study - Nöhre, Mariel; de Zwaan, Martina; Bauer-Hohmann, Maximilian; Ius, Fabio; Valtin, Christina; Gottlieb, Jens (Frontiers in Psychiatry, 2021)
Objectives: It has been recommended that all candidates for lung transplantation undergo pre-transplant psychosocial evaluation for risk assessment. However, psychosocial issues are only important if they correlate with outcomes after transplantation. Methods: In this prospective study patients who were referred for lung transplantation from 2016 to 2018 (n=352) at Hannover Medical School were evaluated using the Transplant Evaluation Rating Scale (TERS). Clinical outcomes included listing, and post-transplant outcomes including mortality, medical aspects such as lung allograft dysfunction, hospitalizations, and renal function, behavioral aspects such as BMI and adherence, and mental issues such as levels of depression, anxiety, and quality of life. TERS scores were divided into tertiles and, in addition, the impact of the 2 subscale scores –“defiance” and “emotional sensitivity”- was investigated. Results: Of the patients who were transplanted (n=271) and were still alive (n=251), 240 had already reached their one-year assessment at the end of 2020 and were evaluated one year after the operation. A subgroup of 143 received an extended mental assessment. BMI, adherence scores, levels of anxiety, depression, and quality of life one year post-transplantation differed significantly between TERS tertiles with higher TERS scores predicting less favorable outcomes. The TERS subscale “defiance” was predictive of BMI and adherence whereas the TERS subscale “emotional sensitivity” was predictive of symptoms of anxiety, depression, and quality of life one year after transplantation. Patients in the lowest TERS tertile were more likely to having been listed and – as a trend - to having survived the first year after transplantation Conclusions: Our findings show that psychosocial factors as measured by TERS score are predictors of behavioral and mental outcomes one year after lung transplantation. The TERS allows us to focus on psychosocial risk factors that can be treated or minimized before or after transplantation.